Mengoptimalkan Penggunaan Media Sosial untuk Meningkatkan Literasi Digital - Karolus Wulla Rato; Yedison Tahey; Yustina Dimu; Antonius M. Ngongo; Yurmin N.A. Kamuri; Yunita Ina; Amandus J. Bulu; Oktavia Nani; Valentino U. Pati; Yakobus B.R. Bombo; Yules Lende; Vediarto Lino; et al. (Jurnal Pengabdian Masyarakat, 2026)
The rapid growth of social media usage among adolescents has transformed how students interact and access information. While social media provides opportunities for learning and communication, its improper use can negatively affect students’ social skills and digital literacy. This community service program aims to optimize the use of social media to enhance digital literacy and foster positive social interactions among students at SMA RARA.The program was implemented through structured workshops, interactive discussions, role-playing exercises, and practical social media activities. Pre- and post-assessments, observations, and feedback forms were employed to evaluate the effectiveness of the program. The results indicate a significant improvement in students’ understanding of responsible social media use, their ability to critically evaluate online information, and their communication skills both online and offline. This program demonstrates that structured guidance and practical activities can transform social media from a mere entertainment platform into a productive educational tool, supporting students’ learning and social development. The findings highlight the importance of integrating digital literacy education into school programs to prepare students for responsible and meaningful engagement in the digital world)